Gyrokinetic simulation of full electromagnetic kinetic ballooning mode in tokamaks - Y. Shen; J.Q. Dong; J. Li; M.K. Han; H.D. He; X.R. Zhang; J.Y. Liu (Nuclear Fusion)
Kinetic ballooning mode (KBM) was simulated and studied numerically by means of a full electromagnetic theory that retains all three gyroscopic fields: $\tilde{φ}$ , $\tilde{A_{||}}$ and $\tilde{B_{||}}$ . The destabilizing influence of the parallel magnetic field fluctuation $δ B_{||}$ on the KBM was reported. When $δ B_{||}$ is neglected, the maximum growth rate decreases by approximately 5% for the magnetohydrodynamic-like ballooning mode (BM), and the growth rates in the higher β region decrease significantly for KBMs with a moderate safety factor ( q ). These are due to the partial cancellation of the stabilizing component of the $\nabla B$ drift by introduction of $δ B_{||}$ effect. Here, β is the ratio of the thermal pressure to magnetic pressure, and $B$ is the toroidal magnetic field. The destabilizing effect of $δ B_{||}$ on KBM is weaker for higher q . Under the influence of toroidal effect, the introduction of the $δ B_{||}$ results in the expansion of the KBM instability window. Compared to the main body of the KBM instability, the extended instability shows partially different features in both the mode- and spectral-structures. For the case of $η_i\unicode{x2A7E} 1$ , the KBM is always unstable in almost the entire region of low shear $\hat {s}$ for a smaller pressure gradient, and the stability boundary in $\hat{s}-α$ plane is much wider than that for the case of $η_i = 0$ . Moreover, the stability boundary of the KBM changes slightly in the $\hat{s}-α$ plane when $δ B_{||}$ is included in the model. All the evidences indicated that β affects KBM through both $δ A_{||}$ and $δ B_{||}$ , and the fundamental properties of KBM are determined by the two gyroscopic fields: $\tilde{φ}$ and $\tilde{A_{||}}$ , while a new $B× \nabla δ B_{||}$ ion drift is introduced by including $δ B_{||}$ to modify the mode characteristics to some extent.